Development of A Telegram Chatbot for Final Project Services Using the Design and Development Research (DDR) Approach - Laisa Nurin Mentari; Tifanny Nabarian; Slamet Santoso; Dymas Sutrysno (Universitas Teknokrat Indonesia, 2026)
Final project administration in higher education involves multiple stakeholders and frequently encounters issues such as delayed information delivery, document inconsistency, and repetitive student inquiries. These problems may increase administrative workload and hinder the final project process. This study aims to analyze user needs and develop a chatbot as an academic information service for final project administration at STT Terpadu Nurul Fikri. The research adopts the Design and Development Research (DDR) approach, focusing on two main stages: Need Analysis and Design and Development. User needs were identified through interviews, observations, and document analysis. Based on the findings, a Telegram-based chatbot was designed and developed using Python and Telegram Bot API integration. The chatbot provides academic etiquette guidelines, general final project information, implementation procedures, schedules, references, and frequently asked questions. The novelty of this study lies in its systematic emphasis on the needs analysis stage as a foundational element for academic chatbot development, which has received limited attention in prior studies. The results indicate that the chatbot has been successfully implemented and deployed as a prototype, serving as a basis for future evaluation and further system enhancement.